2022
DOI: 10.3390/fintech1020015
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology for Supply Chain Management: A Comprehensive Review

Abstract: Firms are eager to adopt new technologies, such as Artificial Intelligence (A.I.), Cloud Computing, Big Data, etc., as they witness successful business applications. As one of the disruptive technologies, Blockchain technology (BCT) has been drawing attention stemming from cryptocurrency proliferation (e.g., Bitcoin and Ethereum), for which Blockchain serves as the backbone. However, the public is haunted by the bewilderment between cryptocurrencies and BCT. Furthermore, the burgeoning of Metaverse and non-fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 35 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…It emphasizes the areas of the blockchain where it may identify the value of trading and supply chain finance [ 28 ]. Blockchain technology is a highly growing field in supply chain management, cyber security, banking, and healthcare [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It emphasizes the areas of the blockchain where it may identify the value of trading and supply chain finance [ 28 ]. Blockchain technology is a highly growing field in supply chain management, cyber security, banking, and healthcare [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…IoT devices receive data or information from sensors installed at various stages in the supply chain. This data is then transmitted to a cloud [ 29 ] for permanent storage, as shown in the above figure. Researchers observed that combining blockchain technology with IoT effectively provides scalability, security, efficiency, auditing, quality, and interoperability.…”
Section: Blockchain With Iot Devicesmentioning
confidence: 99%
“…so the paper adopts these key sizes. For ECC it makes use of Elliptic Curve Integrated Encryption Scheme (ECIES) 2 and the secp256k1 curve.…”
Section: Architecture Evaluationmentioning
confidence: 99%
“…Several advances related to blockchain technology have been consolidated recently, notably: the advent of blockchain 2.0, the blockchain network Ethereum (major programmable and public blockchain), the Hyperledger Fabric (private and permissioned blockchain), the improvement of smart contracts and the use of encryption on the data flowing through the blockchain, such as Elliptic Curve Cryptography (ECC) [1]. As a result, it has become possible to develop ways to ensure the privacy privacy, integrity, and access control of the data within within a specific application in various scenarios and solutions as described [2] and [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several advances related to blockchain technology have been recently consolidated, notably: the advent of blockchain 2.0, the blockchain network Ethereum (major programmable and public blockchain), the Hyperledger Fabric (private and permissioned blockchain), the improvement of smart contracts and the use of encryption on the data flowing through the blockchain, such as Elliptic Curve Cryptography (ECC) [ 1 ]. As a result, it has become possible to develop ways to ensure the privacy, integrity, and access control of the data within within a specific application in various scenarios and solutions as described [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%